Employment adjustments following rises and reductions in minimum wages: new insights from a survey experiment - Bossler, Mario; Oberfichtner, Michael; Schnabel, Claus (Bonn, 2018)
"The effects of large minimum wage increases, like those planned in the UK and in some US states, are still unknown. We conduct a survey experiment that randomly assigns increases or decreases in minimum wages to about 6,000 establishments in Germany and asks the personnel managers about their expectations concerning employment adjustments. We find that employment reacts asymmetrically to positive and negative changes in minimum wages. The larger the increase in the minimum wage is, the larger the expected reduction in employment. Employment adjustments are more pronounced in those industries and plants which are more strongly affected by the current minimum wage and in those plants that have neither collective agreements nor a works council. In contrast, employment is not found to increase if the minimum wage is reduced by about 10 percent. This mainly reflects that plants with works councils and collective agreements would not cut wages."